Factors Influencing Consumers’ Financial Transactions in Islamic Banks Compared with Conventional Banks: Empirical Evidence from Selected Middle-East Countries with a Dual Banking System* - Alemu, Aye Mengistu (African and Asian studies, 2012)
Abstract Despite various evidences that show Islamic banking has gained popularity even by non-Muslim consumers and businesses in many parts of the world, there is still a general misconception that consumer’s choice for Islamic banking is only influenced by religious obligations and thus it is just a Muslim-only affair. Yet, our knowledge of consumer motivations for choosing Islamic versus conventional banking services is modest and the research to date is limited and ambiguous on these key issues. Therefore, this study conducts a two-step empirical analyses and first identifies the factors influencing customer’s decision whether to choose Islamic or conventional banking using Linear Probability Model (LPM) and Tobit estimation method, and as a second step, it investigates the main attributing factors to consumers overall level of satisfaction with the services provided by Islamic banks compared to conventional banks using ordinal-logistic regression model. The study was based on a randomly selected 322 bank customers from Bahrain, Jordan, and UAE. The study confirms that although religious factors such as Shari’a compliance are important, other non-religious factors including better quality of services and information disclosure are also playing crucial roles for the growing consumers’ demand for Islamic banking. Nevertheless; factors such as better rate of return, accessibility to credit, and SMS banking are found to be the main significant determinants of consumers’ choice and satisfaction with the services provided by conventional banks. Overall, the recent experience especially after the financial crisis of 2008 demonstrates that Islamic banking system can be part of the solution since it is mainly based on stronger regulatory system.